(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article analyzes the different views of scientists on the phenomenon of procrastination, considers the main reasons for delaying the solution of problems. The author proves the relevance of studying procrastination as a factor in creating an educational environment in higher education institutions. The aim of the study was chosen theoretical and empirical analysis of the phenomenon of procrastination in the educational activities of students. The significance of motivational insufficiency, perfectionism and anxiety in the structure of procrastination is revealed. The results of an empirical study of the influence of learning motivation on student procrastination are presented. It was stated that the tendency of higher education seekers to postpone solving tasks is not correlated with the age of the respondents.